Parallel imports and problems of the Russian car market ("Journal "U". Economy. Management. Finance.", 2024)
In modern Russia, love for cars is widespread. Every year more and more cars, car manufacturers and brands appear, but not all of them, unfortunately, end up on the Russian market, so some buyers have to import foreign cars themselves. In this article we tried to show the process of importing cars from abroad in different periods of time.
Keywords: parallel import; regulation; tax rate; Russian Federation; import of cars; customs clearance; taxation; car; recycling collection; car market; dealership